Price Determinants of Sparkling Wine in Poland: Does Reputation Really Matter? - Samuele Trestini; Alice Stiletto; Stefanella Stranieri (Wine Economics and Policy)
Due to the important worldwide growth of the sparkling wine sector in the last years, this research aims to explore the Polish sparkling wine retail market by applying a hedonic price model. Poland is the most important market in Eastern Europe, with a noticeable increase in wine consumption in recent years. Few researches have investigated the price premium of wine attributes in this area, while none of these concentrated their analysis on sparkling wines. The aim of this research is to apply a hedonic price model to estimate the effects of credence attributes and quality signals on sparkling wines sold in the Polish capital. Data were collected from 35 retail stores in Warsaw. Findings suggest that collective reputation linked to designation of origin is the variable that most affects the price, followed by brand reputation and characteristics of the point of sale. The type of retailer has a significant effect on price: discounts and supermarkets imply a price decrease with respect to hypermarkets, whereas specialised shops charge a premium. Moreover, we explore the presence of wine with Italian sounding names: this positively affects wine price, confirming the role of imitations stressed in the recent literature.